(untitled) (INTERNATIONAL JOURNAL OF INDUSTRIAL AND PRODUCTION ENGINEERING, 2025)
As cyber threats continue to grow in sophistication and scale, it has become increasingly clear that traditional technology-focused cybersecurity approaches are insufficient on their own. This article advocates for a human-centric cybersecurity paradigm that integrates psychological insights and socio-technical systems thinking to address the complex interplay between human behavior, organizational culture, and technical infrastructure. Drawing on cognitive psychology, behavioral science, and systems engineering, the paper explored key human factors that influence security, such as cognitive limitations, social engineering susceptibility, and security fatigue. It examined the value of user-centered system design, adaptive security measures, and policy frameworks that align with real-world user behavior and organizational dynamics. Additionally, the article outlined a conceptual framework for human-centric cybersecurity and identified future research directions, including the quantification of cognitive biases, evaluation of gamified training, as well as embedding security metrics into organizational performance. Through the promotion of interdisciplinary collaboration and laying emphasis on the central role of human agents, this work aims to guide the development of more resilient, effective, and ethically grounded cybersecurity practices.